The Neighborhood Social Distancing To Prevent Covid-19 In Red Zone of South Tangerang City In Indonesia - Erar Yusuf, Adie; Junaedi Abas, Ahmad (Devotion : Journal of Research and Community Service, 2023)
Covid-19 pandemic has caused deaths and affected the lives of humankind in the world. The Indonesian government has taken numerous measures to respond to the Covid-19 outbreak through social distancing policy called Large Scale Social Restriction. The Task Force for the Acceleration of Covids-19 in the Sub-District Level, Village Level, and Community Unit Level and Neighborhood Unit in the regions is socializing Covid-19 prevention and breaking transmission chain. The main aim of this study was to mapping neighborhood health conditions to prevent and control on Covid-19. In this online survey, a self‐designed questionnaire was distributed among neighborhood unit of urban village in South Tangerang City, Banten, Indonesia. Data were analyzed using descriptive statistic shows that residents in the neighborhood are generally in good health conditions. Some residents suffer from chronic diseases such as hypertension, coronary heart, diabetes, gastric ulcer, and several pregnant woman. The study concludes the importance of resident’s neighborhood solidarity and mutual cooperation by showing discipline and complying with health protocols such as social distancing, and physical distancing as well as maintaining good hygiene